1995
DOI: 10.1111/j.1440-1681.1995.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Responses to Rat Adrenomedullin in Anaesthetized Spontaneously Hypertensive Rats

Abstract: 1. The haemodynamic effects of rat adrenomedullin (AM), a novel hypotensive peptide, were examined in anesthetized 16-18 week old spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY). 2. An intravenous injection of rat AM dose-dependently reduced the mean blood pressure (MBP) with a concomitant fall in total peripheral resistance index (TPRI) and an increase in cardiac index (CI) in both strains of rats. Percent changes in MBP, TPRI and CI were not different between SHR and WKY. 3. The plasma half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…This finding was compatible with the previous report that AM and CGRP exerted a potent vasodilator action via cAMP (7). Although HR was increased by both peptides, implying that reflexive sympathetic activation occurs as a result of both treatments, CI was increased by AM (23,24) but not by CGRP (15,16), in agreement with previous reports. This finding was probably due to the difference in cardiac-afterload reduction between the AM and CGRP groups.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was compatible with the previous report that AM and CGRP exerted a potent vasodilator action via cAMP (7). Although HR was increased by both peptides, implying that reflexive sympathetic activation occurs as a result of both treatments, CI was increased by AM (23,24) but not by CGRP (15,16), in agreement with previous reports. This finding was probably due to the difference in cardiac-afterload reduction between the AM and CGRP groups.…”
Section: Discussionsupporting
confidence: 92%
“…2,11,12 The hypotensive effect of AM observed in those studies was shown to be largely secondary to direct vasodilatation, 11,12 which was further demonstrated by ex vivo studies with isolated rat aorta and with perfused rat mesenteric artery. 13,14 The mechanisms by which AM dilates blood vessels are not completely understood; however, based on the numerous articles published to date, it is clear that AM directly dilates blood vessels of the systemic and pulmonary circulation in an endothelium-dependent or independent manner.…”
Section: Vasodilator Action Of Ammentioning
confidence: 80%
“…The increased vasodilation was associated with a slight increase in glomerular filtration rate and natriuresis in the renal system (8). In the cardiovascular system, Ishiyama et al (9) reported that the Adm peptide, in addition to producing a fall in blood pressure, elicited an increase in cardiac index and stroke volume without a subsequent change in heart rate.…”
Section: Adrenomedullin (Adm)mentioning
confidence: 99%